Manajemen Pembelajaran Guru Pendidikan Jasmani Sekolah Dasar di Kota Bima - Irawan, Ewan; Shandi, Shutan Arie; Salahudin, Salahudin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
Bima town is one of the second level regions in West Nusa Tenggara Province which consists of five districts namely Raba, East Rasanae, West Rasanae, Mpunda and Asakota districts. Through the Department of Education, and along with government programs in academic year 2014/2015 most elementary schools in the Bima town area have adopted a new curriculum, the 2013 curriculum. , sports and health Primary school in the town of Bima. Data collection uses observation, interview, and documentation techniques. The data sources are taken from supervisors, principals, teachers, and students. Data validity is obtained by triangulation. Data were analyzed by (1) data reduction, (2) data presentation, and (3) drawing conclusions. The focus of this research is the management of learning carried out by physical education and physical education teachers in elementary schools in the town of Bima which includes three stages, namely (1) learning planning, (2) implementing learning, and (3) conducting evaluation.Keywords: Learning Management of Physical, Sport, and Health Education